PENGARUH BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DITINJAU BERDASARKAN PEKERJA LAKI-LAKI DAN PEKERJA PEREMPUAN (STUDI KASUS PADA PT. PELINDO MARINE SERVICE SURABAYA) - MALINDA TELMANIER, LUSIANA (Jurnal Ilmu Manajemen (JIM), 2018)
This study aims to analyze the influence of organizational culture and work discipline on employee performance reviewed based on male and female workers at PT. Pelindo Marine Service Surabaya. The population in this study amounted to 85 employees, consisting of 30 female employees and 55 male employees. The results of this study indicate that organizational culture has a significant positive effect on employee performance and organizational culture implementation at PT. Pelindo Marine Service Surabaya between male and female workers does not have significant differences. This can be seen from the result of different test of t-test t value equal to -1,614 <t table 1,989 with probability significance (two tail) 0,110> 0,05 . Work discipline has a significant positive effect on employee performance and implementation of work discipline at PT. Pelindo Marine Service Surabaya between male workers and female workers did not significantly differ from the results of different test t-test t-test value -0.731 <t table 1.989 with probability significance (two tail) 0.467> 0.05. While the calculation of F test jointly organizational culture and work discipline affect the employee performance and on the implementation of employee performance between male employees and female employees of PT. Pelindo Marine Service Surabaya does not have a significant difference this can be seen from the results of different test t-test t count value of 0.762 <t table 1.989 with probability significance (two tail) 0.448> 0.05. Keywords : organizational culture, work discipline, employee performance, gender